Determinants of Inclusive Urban Water Supply: A Data-Driven Analysis of Maiduguri - Abdullahi Babagana; Reuben Jobien Jacob; Yakubu Mohammed (SureBuilt Series, 2026)
Water supply is critical to urban governance and the achievement of SDG 6 and 11. In Maiduguri, rapid urbanisation, weak infrastructures and uneven water distribution have created significant disparities in access despite efforts, particularly in fringe communities. This study examines the factors influencing inclusive water supply in Maiduguri, analysing 381 households across 36 census areas. A two-stage composite index was computed based on source (20%), distribution (50%), and storage (30%). Random Forest regression was utilised to explore the influence of water supply variables on inclusiveness, with Mean Absolute Shapley Additive Explanation (SHAP) values assessing variable significance. The results indicated spatial disparities, with the lowest inclusiveness found in seven fringe census areas. Overall, Maiduguri reached a composite index score of 2.4, reflecting satisfactory inclusiveness. SHAP analysis ranked distance to water source (0.159) and water supply volume per hour per day (0.129) as the main factors affecting inclusiveness. In contrast, the source of water had minimal impact (SHAP value of 0.075). The study recommends modernising outdated infrastructure and installing new, easily monitored pipelines and incorporating socioeconomic factors to improve model robustness. “From Roads to Rigs: Assessing Transport Management and Operational Challenges for Heavy-Duty Equipment Operators in Ghanaian Gold Mining Supply Chains”